2020
DOI: 10.1113/jp279754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of e‐cigarettes and vaping devices on cardiac and pulmonary physiology

Abstract: Short term • Increased flow resistance • Increased airway reactivity Long term • Emphysema • Higher airway resistance • Airway onstruction • Airway inflammation Short term • Increased heart rate • Increased blood pressure • Increased aortic stiffness Long term • Increased atherosclerosis • Increased aortic stiffness Abstract E-cigarette aerosols are exceedingly different from conventional tobacco smoke, containing dozens of chemicals not found in cigarette smoke. It is highly likely that chronic use of e-cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 65 publications
0
45
0
5
Order By: Relevance
“…Lungs represent the main site for aerosol deposition during inhalant use. Several studies have shown the effects of e-cigarettes on lung physiology (7, 29). To determine the effect of chronic JUUL aerosol inhalation on lung physiology, mechanic scans of airways resistance and lung elastance were carried out and were found to be similar across JUUL Mint, JUUL Mango and Air control groups at 1 and 3 months of exposure ( Supplemental Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lungs represent the main site for aerosol deposition during inhalant use. Several studies have shown the effects of e-cigarettes on lung physiology (7, 29). To determine the effect of chronic JUUL aerosol inhalation on lung physiology, mechanic scans of airways resistance and lung elastance were carried out and were found to be similar across JUUL Mint, JUUL Mango and Air control groups at 1 and 3 months of exposure ( Supplemental Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conventional tobacco as well as some e-cigarette aerosol exposures, have been found to cause increased cellularity in the airways (2, 7, 8), and cigarette smoking leads to recruitment of neutrophils to the airways in particular (2). Total leukocyte and neutrophil counts in bronchoalveolar lavage (BAL) of mice exposed to JUUL aerosols for 1 and 3 months were not different than those in Air controls, indicating that inflammatory cell recruitment to the airways was unaffected ( Supplemental Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations